Jawabanmu

Jawaban paling cerdas!
2014-03-06T17:50:20+07:00
A.  U_{1} =  1 (5 - 2×1) = 1 ( 5 - 2) = 1 × 3 = 3
 U_{2} =  2 (5 - 2×2) = 2 ( 5 - 4) = 2 × 1= 2
 U_{3} =  3 (5 - 2×3) = 3 ( 5 - 6) = 3 × (-1) = -3
 U_{4} =  4 (5 - 2×4) = 4 ( 5 - 8) = 4 × (-3) = -12
 U_{5} =  5 (5 - 2×5) = 5 ( 5 - 10) = 5 × (-5) = -25
 U_{6} =  6 (5 - 2×6) = 6 ( 5 - 12) = 6 × (-7) = -42

b.  U_{1} = 1(1 + 3) = 1 × 4 = 4
 U_{2} = 2(2 + 3) = 2 × 5 = 10
 U_{3} = 3(3 + 3) = 3 × 6 = 18
 U_{4} = 4(4 + 3) = 4 × 7 = 28
 U_{5} = 5(5 + 3) = 5 × 8 = 40
 U_{6} = 6(6 + 3) = 6 × 9 = 54

c.  U_{1} = 2×1(1 - 1) = 2×0 = 0
 U_{2} = 2×2(2 - 1) = 4×1 = 4
 U_{3} = 2×3(3 - 1) = 6×2 = 12
 U_{4} = 2×4(4 - 1) = 8×3 = 24
 U_{5} = 2×5(5 - 1) = 10×4 = 40
 U_{6} = 2×6(6 - 1) = 12×5 = 60

d.  U_{1} = 1(1 - 1) /2 = 1×0 /2 = 0/2 = 0
 U_{2} = 2(2 - 1) /2 = 2×1 /2 = 2/2 = 1
 U_{3} = 3(3 - 1) /2 = 3×2 /2 = 6/2 = 3
 U_{4} = 4(4 - 1) /2 = 4×3 /2 = 12/2 = 6
 U_{5} = 5(5 - 1) /2 = 5×4 /2 = 20/2 = 10
 U_{6} = 6(6 - 1) /2 = 6×5 /2 = 30/2 = 15

e.  U_{1} =  1^{2} /(1 + 1) = 1/2
 U_{2} =  2^{2} /(2 + 1) = 4/3 = 1 1/3
 U_{3} =  3^{2} /(3 + 1) = 9/4 = 1 1/9
 U_{4} =  4^{2} /(4 + 1) = 16/5 = 3 1/5
 U_{5} =  5^{2} /(5 + 1) = 25/6 = 4 1/5
 U_{6} =  6^{2} /(6 + 1) = 36/7 = 5 1/7


























1 5 1